Dento-alveolar injury associated with severe extrusive-buco luxation of primary tooth - Dimas Prasetianto Wicaksono; Gifa Alfi Syahrin; Frida Chusna Achirularofa; Udijanto Tedjosasongko; Kittipong Laosuwan; Soegeng Wahluyo (Faculty of Dental Medicine Universitas Airlangga, 2026)
Background: Traumatic dental injury in primary tooth is one of damaging of primary tooth and surrounded tissues due to physical impact. This damage often occurs in children and adolescent due to fall, sport activity or accident. The impact of this injury in several cases not only involving just the tooth, but also surrounded tissue such as periodontal tissue, gingiva. One of the traumatic dental injuries in primary tooth aim is preventing the damaging of permanent tooth bud, then the treatment of this injury should be done in quick and appropriate. Purpose: to present the management of dento-aveolar injury with severe extrusive-buco lateral luxation in primary tooth. Case: A female toddler 2 years old came to the outpatient, Department of Pediatric Dentistry, Universitas Airlangga to treat his complaint. She was complained mobility of her incisive together with difficulties to eat. Based on the history, she went to dental emergency room 2 days earlier, Academic Dental Hospital, Universitas Airlangga due to falling down the stairs at her home. After getting treatment in emergency room, she was referred to pediatric dentistry department. Case Management: The diagnose of her complain was dento-aveolar injury with severe extrusive-buco lateral luxation on primary mandibular left central incisor (71) and traumatic ulcer on left lower labial. Extraction of tooth 71 was the option to treat her complain, together with administration some medicines. Conclusion: Extraction is the option for severe extrusive buco-lateral luxation in a primary tooth to restore function, prevent aspiration and permanent tooth bud damage.